2018
DOI: 10.1007/s00374-018-1302-9
|View full text |Cite
|
Sign up to set email alerts
|

Methanotrophs are favored under hypoxia in ammonium-fertilized soils

Abstract: Methanotrophy of arable soils is affected by N fertilization, but the knowledge about the effect of oxygen level is poorly understood; soil aeration can fluctuate and zones of low oxygen are widespread in soil. We monitored CH 4 oxidation in three mineral soils (Eutric Cambisol, Haplic Podzol, Mollic Gleysol) under laboratory conditions by varying the O 2 level (from 20 to 2% O 2), with or without NH 4 + (100 mg N kg −1). In controls (without NH 4 +), CH 4 was oxidized completely in the O 2 range from oxia (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…The affinity of the methane monooxygenase enzyme for CH 4 is, however, 600-to 1,300-fold higher than the affinity for NH + 4 , so we expect this effect to be of little influence. Generally, ammonium stimulates methanotroph growth and protein synthesis by providing bioavailable nitrogen (Bodelier et al, 2000), although recent research in soils found a decrease in methane oxidation rates after ammonium addition (Walkiewicz et al, 2018). Nitrate has also been suggested in earlier studies to inhibit methane oxidation under oxic conditions (Geng et al, 2017;Walkiewicz and Brzezinska, 2019), although the observed effect in those studies could have been due to the high salt concentrations, not specifically nitrate (Dunfield and Knowles, 1995), or due to the conversion of nitrate to nitrite (Roco et al, 2016), which is known to be an inhibitor of methane oxidation (Dunfield and Knowles, 1995;Hutsch, 1998).…”
Section: Role Of Nitrate and Ammonium In Methane Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…The affinity of the methane monooxygenase enzyme for CH 4 is, however, 600-to 1,300-fold higher than the affinity for NH + 4 , so we expect this effect to be of little influence. Generally, ammonium stimulates methanotroph growth and protein synthesis by providing bioavailable nitrogen (Bodelier et al, 2000), although recent research in soils found a decrease in methane oxidation rates after ammonium addition (Walkiewicz et al, 2018). Nitrate has also been suggested in earlier studies to inhibit methane oxidation under oxic conditions (Geng et al, 2017;Walkiewicz and Brzezinska, 2019), although the observed effect in those studies could have been due to the high salt concentrations, not specifically nitrate (Dunfield and Knowles, 1995), or due to the conversion of nitrate to nitrite (Roco et al, 2016), which is known to be an inhibitor of methane oxidation (Dunfield and Knowles, 1995;Hutsch, 1998).…”
Section: Role Of Nitrate and Ammonium In Methane Oxidationmentioning
confidence: 99%
“…Air was, however, injected into the microoxic and trace oxygen incubation bottles on days 2, 6, and 13 in order to prevent oxygen depletion. Despite being aerobes, methanotrophs are generally assumed to be (partially) inhibited by oxygen concentrations >60 µM or at least stimulated by low-oxygen conditions (Rudd and Hamilton, 1975;Van Bodegom et al, 2001;Danilova et al, 2016;Walkiewicz et al, 2018;Thottathil et al, 2019;Walkiewicz and Brzezinska, 2019), resulting in a low methane oxidation efficiency at high oxygen concentrations. A recent study by Thottathil et al (2019) stated that methane oxidation rates are only at 20% of their maximum value at oxygen saturation and that the fact that this oxygen inhibition is generally not considered for global models may offset the total methane oxidation potential calculations greatly, expressing the need for additional studies on the response of methanotrophs to different oxygen concentrations.…”
Section: Methylobacter Sp Under Oxygen Limitationmentioning
confidence: 99%
“…Therefore, the CH 4 emissions were not significant until the anoxic fractions of the soil dominated. The hypoxia in agricultural soils usually favored the methanotrophs, which is the major contributor for CH 4 oxidation 56 , thus CH 4 emission rates increased dramatically once the hypoxic fraction declined to the minimum.…”
Section: Discussionmentioning
confidence: 99%
“…The soils were characterized by similar air-water conditions, as a result of their similar textures (sandy loam and loamy sand). The main difference between the soils was the C org content (Walkiewicz et al, 2018;Wnuk et al, 2017). The basic properties of the tested soils are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%